2016
DOI: 10.1108/ijccsm-12-2014-0148
|View full text |Cite
|
Sign up to set email alerts
|

Growth impact of CO2emissions caused by tourist arrivals in Turkey

Abstract: Purpose – The purpose of this study is to analyze the determinants of changes in carbon dioxide (CO2) emissions for Turkey by utilizing the autoregressive distributed lag approach to investigate the long-run equilibrium relationships of CO2 emissions between foreign tourist arrivals (FTAs) and electricity consumption (ELC). The results reveal that foreign tourists and ELC are significant determinants of a long-run equilibrium relationship with CO2 emissions from electricity and heat production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
(57 reference statements)
2
16
0
3
Order By: Relevance
“…The academia has produced considerable research on tourism. However, the majority of these studies independently analyzed domestic and international tourists and found few differences in the natural environment, local government policies, and other factors that affect domestic and international tourists [6][7][8][9][10][11][12][13][14]. This paper argues that tourists are mainly categorized into two major groups, namely, domestic and international.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The academia has produced considerable research on tourism. However, the majority of these studies independently analyzed domestic and international tourists and found few differences in the natural environment, local government policies, and other factors that affect domestic and international tourists [6][7][8][9][10][11][12][13][14]. This paper argues that tourists are mainly categorized into two major groups, namely, domestic and international.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we mainly consider two major categories of factors, namely air (environment) quality factors such as carbon dioxide (CO 2 ) emissions and PM 2.5 concentrations; and government economic policies such as market-oriented, urbanization, foreign trade, and transportation construction policies. Research has been previously conducted on these factors [7][8][9][12][13][14]16]. Although these studies provide a basis for us to understand the impact of these factors on tourism, we aim to investigate whether these effects differ across domestic and foreign visitors.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches of these studies can be classified into four categories: decomposition analysis [13][14], bottomup analysis [15][16], system optimization [17][18], and econometric approaches [19][20]. Decomposition analysis is the most commonly used method, which encompasses two main decomposition techniques: structural decomposition analysis (SDA) [13] and index decomposition analysis (IDA) [14].…”
mentioning
confidence: 99%
“…The third method has been utilized to study the major influencing factors of CO 2 emissions for the European food industry [17], and explore the effect of renewable energy on CO 2 emissions of Japan [18]. The autoregressive distributed lag (ARDL) model [19] and vector autoregression (VAR) model [20] are the two common methods of econometric approaches. Yorucu [19] applied the ARDL model to investigate the influence of electricity consumption and foreign tourist arrivals on CO 2 emissions in Turkey's transport industry.…”
mentioning
confidence: 99%
See 1 more Smart Citation